Fluorescence nanoscopy in whole cells by asynchronous localization of photoswitching emitters. - Egner, A; Geisler, C; von Middendorff, C; Bock, H; Wenzel, D; Medda, R; Andresen, M; Stiel, A; Jakobs, S; Eggeling, C; Schönle, A; Hell, S (2007)
We demonstrate nanoscale resolution in far-field fluorescence microscopy using reversible photoswitching and localization of individual fluorophores at comparatively fast recording speeds and from the interior of intact cells. These advancements have become possible by asynchronously recording the photon bursts of individual molecular switching cycles. We present images from the microtubular network of an intact mammalian cell with a resolution of 40 nm.